Locked homes empty schools : the impact of distress seasonal migration on the rural poor - Smita; Panjiar, Prashant (New Delhi : Zubaan, 2006)
Study on the migrant labour and their children with a pictorial representation
Includes bibliographical references
Keywords: Migrant labour -- India; Children of migrant labourers -- India